1986
DOI: 10.1070/qe1986v016n04abeh006527
|View full text |Cite
|
Sign up to set email alerts
|

Mode-locked generation of transverse modes in a neodymium laser with a positive electrooptic feedback

Abstract: We discuss a universal bound on any excitation of heavy fields during inflation: the ratio of the heavy field's energy density to the one driving inflation must be less than the maximally allowed relative amplitude of oscillations in the power-spectrum (ρ h /ρ I 0.01 according to PLANCK). This bound can be traced back to the sudden change of the equation of state parameter across the excitation event.We employ a sudden transition approximation at the perturbed level, which has been used before in different set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In summary, we have demonstrated the successful transverse mode-locking of an end-pumped solid-state laser with an acousto-optic modulator. Compared to previous publications [2,[5][6][7] we provided an advanced analysis of the transverse mode-locked (TML) laser by reconstructing the modal power coefficients and the modal phases of the generated laser beams with the stochastic parallel gradient descent algorithm. Based on these reconstructions, we found that with the presented setup the average mode order n could be freely adjusted up to a value of 31.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, we have demonstrated the successful transverse mode-locking of an end-pumped solid-state laser with an acousto-optic modulator. Compared to previous publications [2,[5][6][7] we provided an advanced analysis of the transverse mode-locked (TML) laser by reconstructing the modal power coefficients and the modal phases of the generated laser beams with the stochastic parallel gradient descent algorithm. Based on these reconstructions, we found that with the presented setup the average mode order n could be freely adjusted up to a value of 31.…”
Section: Discussionmentioning
confidence: 99%
“…Auston showed that by locking the phases of multiple Hermite-Gaussian (HG) modes a fast scanning beam, oscillating in the transverse direction of the optical axis, could be generated. Since this initial demonstration of transverse mode-locking in a He-Ne laser the successful locking of transverse modes was also realized in semiconductor [5] and solid-state lasers [6,7]. However, in these experiments the transverse mode-locking was only obtained over limited time periods as the lasers were either Q-switched or pumped by a pulsed laser source.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scanning frequency of such TML lasers only depends on the transverse mode spacing of the laser and can, therefore, achieve high spot resolving rates in the multi-GHz regime [20]. Since transverse mode locking was suggested [18] and demonstrated [19] for the first time in a He-Ne laser, it has also been realized in semiconductor [21] and solid state lasers [22,23]. Furthermore, the simultaneous locking of longitudinal and transverse modes has been demonstrated [24][25][26].…”
Section: Introductionmentioning
confidence: 99%